Answer:
The answer is: y = 2/3x - 3
Explanation:
Given point: (3, -1)
Given equation: y = 2/3x - 5, which is in the form y = mx + b where m is the slope and b is the y intercept.
Parallel lines have the same slope. Use the point slope form of the equation with the point (3, -1) and substitute:
y - y1 = m(x - x1)
y - (-1) = 2/3(x - 3)
y + 1 = 2/3x - 6/3
y + 1 = 2/3x - 2
y = 2/3x - 3
Proof:
f(3) = 2/3(3) - 3
= 6/3 - 3
= 2 - 3
= -1, giving the point (3, -1)
Hope this helps! Have an Awesome Day!! :-)